Mycobacterium tuberculosis infection in health care workers in rural India: comparison of a whole-blood interferon gamma assay with tuberculin skin testing - Pai, Madhukar; Gokhale, Kaustubh; Joshi, Rajnish; Dogra, Sandeep; Kalantri, Shriprakash; Mendiratta, Deepak K; Narang, Pratibha; Daley, Charles L; Granich, Reuben M; Mazurek, Gerald H; Reingold, Arthur L; Riley, Lee W; et al. (JAMA : the journal of the American Medical Association, 2005)
Mycobacterium tuberculosis infection in health care workers has not been adequately studied in developing countries using newer diagnostic tests. To estimate latent tuberculosis infection prevalence in health care workers using the tuberculin skin test (TST) and a whole-blood interferon gamma (IFN-gamma) assay; to determine agreement between the tests; and to compare their correlation with risk factors. A cross-sectional comparison study of 726 health care workers aged 18 to 61 years (median age, 22 years) with no history of active tuberculosis conducted from January to May 2004, at a rural medical school in India. A total of 493 (68%) of the health care workers had direct contact with patients with tuberculosis and 514 (71%) had BCG vaccine scars. Tuberculin skin testing was performed using 1-TU dose of purified protein derivative RT23, and the IFN-gamma assay was performed by measuring IFN-gamma response to early secreted antigenic target 6, culture filtrate protein 10, and a portion of tuberculosis antigen TB7.7. Agreement between TST and the IFN-gamma assay, and comparison of the tests with respect to their association with risk factors. A large proportion of the health care workers were latently infected; 360 (50%) were positive by either TST or IFN-gamma assay, and 226 (31%) were positive by both tests. The prevalence estimates of TST and IFN-gamma assay positivity were comparable (41%; 95% confidence interval [CI], 38%-45% and 40%; 95% CI, 37%-43%, respectively). Agreement between the tests was high (81.4%; kappa = 0.61; 95% CI, 0.56-0.67). Increasing age and years in the health profession were significant risk factors for both IFN-gamma assay and TST positivity. BCG vaccination had little impact on TST and IFN-gamma assay results. Our study showed high latent tuberculosis infection prevalence in Indian health care workers, high agreement between TST and IFN-gamma assay, and similar association between positive test results and risk factors. Although TST and IFN-gamma assay appear comparable in this population, they have different performance and operational characteristics; therefore, the decision to select one test over the other will depend on the population, purpose of testing, and resource availability.